RANCANG BANGUN APLIKASI PEMESANAN PRODUK PADA SYUKUR ALUMUNIUM - Sapri, Sapri (Jurnal Media Infotama, 2021)
Inventory management, to carry out searches, additions and subtractions, it is very necessary to have a computer so that what is needed to manage inventory becomes better. Amanah Variation is an independently owned business entity which operates in the field of vehicle variation installation services and accessory sales. Because there are many kinds and types of goods being sold, as well as the large number of goods available, the longer it goes on, the more difficult it will be to search and find out the number of each type and type of goods owned. Therefore, it is necessary to have tools (programs) that will be able to solve various inventory management problems. Spare parts or what are called spare-parts are usually not always readily available on the market but are very limited. These spare parts are supporting tools for machines that are used to produce a product so that spare parts have a very vital role in the continuity of the production process in every manufacturing company. This program can be used on an ongoing basis, it will provide a lot of assistance in completing administration and inventory control. ) existing spare parts. This is because by using this program, the process is faster and more controlled. It is also easy to operate, so operators who are tasked with using the program do not experience many difficulties.